1990
DOI: 10.3109/02713689009000051
|View full text |Cite
|
Sign up to set email alerts
|

Microcarrier cell culture of neonatal human corneal endothelium

Abstract: Fresh isolates of neonatal human corneal endothelial cells were maintained in tissue culture using a technique employing collagen-coated, dextran-based microcarrier beads. This method provides large yields of endothelial cells suitable for biochemical and/or transplant studies without exposing the cells to enzymatic passage. Our results suggest that microcarrier culture of human corneal endothelial cells can provide a useful in vitro system for the growth and maintenance of actively mitotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…[3][4][5][6] Previous studies showed that HCECs can be successfully cultured by the stimulation of growth factors. [7][8][9][10][11][12] This means that HCECs do not lose their proliferative capacity, but retain the potential to proliferate. Previous studies in our laboratory revealed that there are age-related differences in the proliferative capacity of HCECs.…”
mentioning
confidence: 99%
“…[3][4][5][6] Previous studies showed that HCECs can be successfully cultured by the stimulation of growth factors. [7][8][9][10][11][12] This means that HCECs do not lose their proliferative capacity, but retain the potential to proliferate. Previous studies in our laboratory revealed that there are age-related differences in the proliferative capacity of HCECs.…”
mentioning
confidence: 99%
“…Although the HCECs have limited proliferative capacity in vivo , these cells have the ability to proliferate under in vitro culture conditions [ 18 , 25 , 29 , 30 , 31 , 32 , 36 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ,…”
Section: Cell Sources For Tissue Engineering Of Corneal Endotheliumentioning
confidence: 99%
“…There are many different types of coating materials available for expansion of HCECs. These include collagen [ 28 , 56 , 65 , 74 , 90 , 93 , 97 , 99 , 110 , 139 ], fibronectin [ 59 , 90 , 93 , 97 , 110 ], gelatin [ 32 , 50 , 76 , 94 ], laminin [ 93 , 97 ], extracellular matrix (ECM) from cultured bovine corneal endothelial cells [ 25 , 27 , 59 , 67 , 71 , 93 ], a mixture of laminin and chondroitin sulfate [ 51 ], and a mixture of fibronectin, collagen, and albumin (FNC Coating Mix ® ) [ 97 , 101 ].…”
Section: Substrates For Cultivation Of Human Corneal Endothelial Cmentioning
confidence: 99%
“…Due to donor shortage, corneal endothelial tissue engineering is a promising alternative to corneal transplantation [ 3 ]. As early as 1990, Insler et al have reported a method to transplant corneal endothelial cells (CECs) expanded ex vivo on the carriers made of collagen-coated dextran [ 4 ]. In recent years, naturally occurring biopolymer such as chitosan has also been widely used to engineer CEC culture substrates.…”
Section: Introductionmentioning
confidence: 99%